Temporal Factors Modulate Haloperidol-Induced Conditioned Catalepsy - Cárcel, Lucía; De la Casa, Luis G. (Frontiers in Behavioral Neuroscience, 2021)
Repeated pairings of a neutral context and the effects of haloperidol give rise to conditioned catalepsy when the context is subsequently presented in a drug-free test. In order to confirm whether this response is based on Pavlovian processes, we conducted two experiments involving two manipulations that affect conditioning intensity in classical conditioning procedures: time of joint exposure to the conditioned and the unconditioned stimulus, and the length of the inter-stimulus interval. The results revealed that both an increase in the length of context-drug pairings during conditioning and a reduced inter-stimulus interval between drug administration and context exposure increased conditioned catalepsy. These results are discussed in terms of the temporal peculiarities of those procedures that involve drugs as the unconditioned stimulus along with the role of Pavlovian conditioning in context-dependent catalepsy.